2009
DOI: 10.4143/crt.2009.41.2.108
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Treatment of Primary Extraskeletal Ewing's Sarcoma of the Chest Wall: Report of 2 Cases

Abstract: Extraskeletal Ewing's sarcoma (EES) is a type of Ewing's sarcoma that arises in soft tissue and is now regarded as a member of a family of small round cell neoplasms of bone and soft tissue, including primitive neuroectodermal tumors (PNETs). EES occurs predominantly in adolescents and young adults between the ages of 10 and 30 years. The disease follows an aggressive course with a high recurrence rate. The presence of a distant metastasis is also common. EES arises in the soft tissue of either the trunk or ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 8 publications
(8 reference statements)
0
18
0
Order By: Relevance
“…Osteosarcomas and round cell tumours (Ewing sarcoma) can involve scapula and usually present as painful masses. Both of these have a bimodal age presentation and can affect young as well as elderly population 8 11…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Osteosarcomas and round cell tumours (Ewing sarcoma) can involve scapula and usually present as painful masses. Both of these have a bimodal age presentation and can affect young as well as elderly population 8 11…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Expression of the MIC2 gene is path-gnomonic for Ewing's sarcoma, but it may also occur in some cases of Tlymphoblastic lymphoma, poorly differentiated synovial sarcoma, small cell osteosarcoma and rhabdomyosarcoma. Ewing's sarcoma can be definitively diagnosed by detection of the EWS gene and rearrangement of ETS-related cancer genes [6].…”
Section: Case Reportmentioning
confidence: 99%
“…Multidrug chemotherapy is more effective than single-drug chemotherapy for the treatment of Ewing's sarcoma. It has been demonstrated that preoperative chemotherapy with the use of a combination of vincristine, doxorubicine, cyclophosphamide and etoposide allows for conservative surgical resection in selected cases with subsequent improvement of the postoperative condition [6].…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…1 About 82 cases of cutaneous or subcutaneous ES reported in the literature. 2 We are reporting this case because of the rarity of this tumor.…”
Section: Introductionmentioning
confidence: 99%